Business performance and competitiveness levels in MSMEs producing footwear in the Cevallos canton - Cisneros Martínez, Marco (2018)
This work reflects the competitiveness condition of the SMEs that produce footwear in Cevallos. It was based on a previous study of the managerial performance and their strategies of production. There were taken 15 enterprises as a reference and through a statistical analysis it was observed areas such as: strategic planning, production and operations supply, logistics quality assurance, human resources, environmental management, accounting and auditing. The obtained results showed that their level of competitiveness gets on well with locally without any difficulty, but they don’t have the appropriate conditions to get into and international market. DOI: https://doi.org/10.31164/bcoyu.17.2018.667 URL: http://revistas.uta.edu.ec/erevista/index.php/bcoyu/article/view/667